Investigation of the temperature dependent field emission from individual ZnO nanowires for evidence of field-induced hot electrons emission. (11th July 2018) - Chen, Yicong; Zhang, Zhipeng; Li, Zhibing; She, Juncong; Deng, Shaozhi; Xu, Ningsheng; Chen, Jun
Abstract: ZnO nanowires as field emitters have important applications in flat panel display and x-ray source. Understanding the intrinsic field emission mechanism is crucial for further improving the performance of ZnO nanowire field emitters. In this article, the temperature dependent field emission from individual ZnO nanowires was investigated by an in situ measurement in ultra-high vacuum. The divergent temperature-dependent Fowler–Nordheim plots is found in the low field region. A field-induced hot electrons emission model, that takes into account penetration length, is proposed to explain the results. The carrier density and temperature dependence of the field-induced hot electrons emission current are derived theoretically. The obtained results are consistent with the experimental results, which could be attributed to the variation of effective electron temperature. All of these are important for a better understanding on the field emission process of semiconductor nanostructures.